ANALISIS KOMPARATIF KUALITAS PENDIDIKAN DI SINGAPURA, INDONESIA, DAN TIMOR LESTE - Allya Septia Faradina; Linda Sukmawati, Alvina Elysia Rizky, Putri Ayu Bestari, Ratna Ayu Antika Puri, Yoga Fernando Rizqi (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This article discusses the quality of education in Singapore, Indonesia, and Timor Leste. The purpose of writing this article is to conduct a comparative analysis of the quality of education in Singapore, Indonesia, and Timor Leste, by exploring the factors that influence the quality of education in each country, including curriculum, teacher quality, and educational facilities. Singapore has an excellent education system with a comprehensive curriculum, high-quality teachers, and modern educational facilities. Indonesia faces challenges in improving the quality of education, such as a curriculum that is not fully aligned with local needs, low teacher quality, and inadequate educational facilities in some areas. Timor Leste, as a newly independent country, is still in the process of building a quality education system with constraints such as a non-standardized curriculum, inadequate teacher quality, and limited educational infrastructure.